2015
DOI: 10.1007/s00464-015-4498-x
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage revision from gastric band to gastric bypass or sleeve gastrectomy: 6- and 12-month outcomes

Abstract: Single-stage revision from LAGB to LRYGB or LSG is technically feasible, but not without complications. The complications in the bypass group were more severe. There was no difference in readmission or reoperation rates, weight loss or comorbidity reduction. Revision to LRYGB trended toward higher rate and greater severity of complications with equivalent weight loss and comorbidity reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…It is also important to mention that WR is associated with the deterioration of the quality of life and the reappearance or worsening of obesity-associated comorbidities, e.g., hypertension and type 2 diabetes (T2D) which necessitate close monitoring and appropriate management [7,8]. Moreover, revisional BS to manage WR/IWL may have higher complication and mortality rates compared to primary BS [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…It is also important to mention that WR is associated with the deterioration of the quality of life and the reappearance or worsening of obesity-associated comorbidities, e.g., hypertension and type 2 diabetes (T2D) which necessitate close monitoring and appropriate management [7,8]. Moreover, revisional BS to manage WR/IWL may have higher complication and mortality rates compared to primary BS [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…There have been recent trends towards RLSG after GB failure, given its comparable WL results [ 10 16 ]. Compared to the complication risks of revision gastric bypass, the complication risks of RLSG are similar in some studies [ 11 , 16 , 17 ] but lower in other studies [ 13 , 15 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 83%
“…Resting pressure high, relaxes properly 92% peristaltic, 8% simultaneous, 0% failed a Full HRM report not available in patient's medical record, but normal results were documented by her surgeon the surgical literature is the 1-stage vs. 2-staged operative approach to conversions after failed LAGB. While roughly 60% of our AGB-to-SG and 65% of our AGB-to-RYGB conversions were done in 2 stages ( Table 2), 60% of patients (n = 1223) in a recent systematic review by Sharples et al (10) and ≥ 70% of patients across multiple US studies have undergone 1-stage conversions as shown in Table 5 [12][13][14][15][16][17][18][19][20][21]. There is no level I evidence supporting the superiority of a staged approach for revisional bariatric surgery following AGB removal.…”
Section: Discussionmentioning
confidence: 99%